Trends and Challenges In The Development of Civil Society In Uzbekistan - Normurodov, Dilshod (Indonesian Journal Publisher, 2025)
Measures to deepen democratic transformations in Uzbekistan are characterized by gradual progress towards the formation of a civil society, the development of the country's state, legal and political system, and the creation of conditions for the free functioning of civil society institutions. This article analyzes the socio-political, legal, and economic issues in the process of building civil society in Uzbekistan, the reforms aimed at addressing these issues, and the role of the state's support in these reforms. The article examines the role of important civil society institutions, such as non-governmental non-profit organizations (NGOs) and mass media, their support by the state, citizen participation, and the challenges faced in developing the activities of these institutions.